Analysis of the Influence of Product Quality, Price, and Promotion on Consumer Satisfaction - Ifan Sadewa (Greenation Management and Business Review, 2025)
This study aims to analyze the effect of product quality, price, and promotion on consumer satisfaction. Using a quantitative approach and multiple linear regression analysis, data were collected from 100 respondents who had used the product. The results show that product quality, price, and promotion each have a significant positive effect on consumer satisfaction. Among the three variables, product quality has the strongest influence, followed by price and promotion. The coefficient of determination (R²) indicates that 68.3% of the variation in consumer satisfaction can be explained by these three factors. These findings suggest that improving product quality, offering reasonable prices, and implementing effective promotional strategies are key to enhancing consumer satisfaction and loyalty. Businesses are encouraged to focus on these aspects to remain competitive and responsive to consumer expectations.